Produção e adição de bactérias biomineralizadoras em concretos de construção civil: estudos preliminares - Costa, Alex Monserrat Pereira (2022)
Knowing the behaviour of a concrete is necessary after finishing a construction work; despite having high mechanical strength under compression stress, its mechanical tensile strength is low, making necessary the search for solutions to solve such problem. Concrete is composed of a mixture of water, cement, fine and coarse aggregates as well as additives, used to improve the concrete characteristics and properties. On-site, it is mostly molded with an embedded steel reinforcing bars completing the strength in all direction. When placed under great amount of stress, it is not seldom that the fissures are generated on concrete, which is the main initial issue that may cause structure-wear leading it to a loss of efficiency. The addition of bacteria capable of producing biomineralization, process in which calcium carbonate is produced and responsible for sealing fissures, has been investigated. Nevertheless, these bacteria are fragile and susceptible to the reaction medium, requiring protection by encapsulation that allows the bacteria to execute the biomineralization when required. Given that, this research aims to use biomineralizing bacteria encapsulated with sodium alginate, to produce samples of concrete without the addition of the capsules and characterize them according to their physical and rheological properties. Swelling tests indicated that the capsules produced provided an adequate environment to receive the bacteria and nourish them until their use; also demonstrated that sodium alginate capsules have a mechanical resistance that supports their insertion (and mixing) in concrete. Among the conditions investigated, the one where the Andreassen coefficient equal to q=0.37 and with the addition of 1.5% of capsules was the one that presented the most promising results of the research; after 28 days of cure, the mechanical resistance to compression was 45.38MPa, being the value within ABTN NBR 11578, since it establishes a minimum resistance of 32MPa.